La dimension économique dans le découpage régional au Maroc : analyse de la convergence des régions - Omar Benida; Khalil Allali; Hassan Ramou; Aziz Fadelaoui (African Scientific Journal, 2023)
This article will diagnose the extent to which the latest regional division in Morocco can allow for better convergence along with economic of regions. To do this, we used econometric modeling based on the σ-convergence test and β-convergence estimation. The study period considered is between 2004 and 2019 partitioned over 3 sub-periods of 5 years each. This allowed for 36 observations for absolute beta-convergence and for conditional beta-convergence. The test used is the Hausman test which grants us to test the presence or absence of a correlation between the specific effects and the explanatory variables of the model. The main results of this modeling are (i) the unconditional σ-convergence and beta- convergence do not prove the existence of convergence but rather divergence between regions, (ii) the conditional β-convergence was able to demonstrate convergence between regions. This can be explained by the fact that conditional β-convergence is only a necessary but not a sufficient condition to achieve the decrease in dispersion between regions in the sense of σ-convergence, (iii) the analysis shows that the regional division does not favor a convergence between regions and thus delays a sustainable economic takeoff of regions.